Thyroid Dysfunction and Risk of Parkinson’s Disease: A Systematic Review and Meta-Analysis - Charoenngam, Nipith; Rittiphairoj, Thanitsara; Ponvilawan, Ben; Prasongdee, Klaorat (Frontiers in Endocrinology, 2022)
Objective: Studies have suggested that patients with thyroid dysfunction may have an increased risk of developing Parkinson’s disease (PD). However, the results from existing studies are inconsistent. Therefore, we aimed to investigate the association of hypothyroidism and hyperthyroidism with risk of PD using the method of systematic review and meta-analysis. Methods: Potentially eligible studies were identified from Medline and EMBASE databases from inception to December 2021 using search strategy that comprised of terms for “Thyroid” and “Parkinson’s Disease”. Eligible cohort study must consist of one cohort of patients with hypothyroidism/hyperthyroidism and another cohort of individuals without hypothyroidism/hyperthyroidism. Then, the study must report effect estimates with 95% confidence intervals (95% CIs) comparing incident PD between the groups. Eligible case-control studies must include cases with PD and controls without PD. Then, the study must explore their history of hypothyroidism/hyperthyroidism. Odds ratio (OR) with 95% CIs of the association between presence of hypothyroidism/hyperthyroidism and PD must be reported. Point estimates with standard errors were retrieved from each study and were combined together using the generic inverse variance method. Results: A total of 3,147 articles were identified. After two rounds of independent review by three investigators, 3 cohort studies and 6 case-control studies met the eligibility criteria and were included into the meta-analysis. Pooled analysis showed an increased likelihood of PD in both patients with hypothyroidism (pooled OR 1.56; 95%CI, 1.38 – 1.77; with moderate heterogeneity, I2 66.9%) and patients with hyperthyroidism (pooled OR 1.57; 95%CI, 1.40 – 1.77; with insignificant heterogeneity, I2 0.0%). Funnel plots for both meta-analyses were fairly symmetric, which did not indicate presence of publication bias. Conclusion: This systematic review and meta-analysis found a significant association of both hypothyroidism and hyperthyroidism with an increased risk of PD.